2002
DOI: 10.1002/ar.10146
|View full text |Cite
|
Sign up to set email alerts
|

Brain expansion in the chick embryo initiated by experimentally produced occlusion of the spinal neurocoel

Abstract: The brain expands in the early chick embryo from pressure generated by accumulation of cerebrospinal fluid (CSF) in a closed neural tube. The sealing of the neural tube occurs as the result of occlusion of the spinal neurocoel rostral to and before closure of the posterior neuropore. We have previously demonstrated the dependence of normal brain expansion upon intraluminal pressure.We had yet to demonstrate, however, that brain expansion actually depends upon natural occlusion of the spinal neurocoel. To demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 19 publications
(35 reference statements)
0
26
0
1
Order By: Relevance
“…It was therefore suggested that zebrafish brain ventricle defects developed secondarily to the circulation defect (Schier et al, 1996). This reasoning also stemmed from studies in chick, which showed that after the onset of circulation a positive CSF pressure inside the brain ventricles is necessary for brain ventricle expansion (Desmond, 1985;Desmond and Jacobson, 1977;Desmond and Levitan, 2002).…”
Section: Two Distinct Periods During Initiation and Expansion Of Braimentioning
confidence: 98%
See 1 more Smart Citation
“…It was therefore suggested that zebrafish brain ventricle defects developed secondarily to the circulation defect (Schier et al, 1996). This reasoning also stemmed from studies in chick, which showed that after the onset of circulation a positive CSF pressure inside the brain ventricles is necessary for brain ventricle expansion (Desmond, 1985;Desmond and Jacobson, 1977;Desmond and Levitan, 2002).…”
Section: Two Distinct Periods During Initiation and Expansion Of Braimentioning
confidence: 98%
“…This dilation pattern is highly conserved in all vertebrates. Elegant studies in chick embryos have shown that intraluminal pressure resulting from the accumulation of CSF inside the brain ventricles is necessary for normal brain ventricle expansion and cell proliferation (Desmond, 1985;Desmond and Levitan, 2002), and levels of proteoglycans such as chondroitin sulfate affect this process (Alonso et al, 1998; The mechanisms by which the vertebrate brain develops its characteristic three-dimensional structure are poorly understood. The brain ventricles are a highly conserved system of cavities that form very early during brain morphogenesis and that are required for normal brain function.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that this is achieved by a combination of increased production of eCSF by neuroepithelial (ependymal) cells, which also function as neural stem cells (Desmond and Levitan, 2002;Johansson et al, 1999;Lowery and Sive, 2005;Mirzadeh et al, 2008;Meletis et al, 2008;Hamilton et al, 2009;Guo et al, 2011) and/or restriction of neuroepithelial permeability (Chang et al, 2012;Fossan et al, 1985;Lowery and Sive, 2009;Whish et al, 2015). While the mechanisms regulating the ventricular lining remain unclear, the expression of voltage-gated potassium (K v ) channels by ependymal cells might be essential due to their role in cell proliferation (Smith et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As the tube is closed it also forms three vesicles anterior to posterior: the prosencepalon/forebrain, the mesencephalon/midbrain and the rhombencephalon/hindbrain. Expansion of the brain now rapidly occurs regulated by an increase in intraluminal pressure created by an increase in CSF (Desmond & Jacobson, 1977;Pacheco et al, 1986;Desmond & Levitan, 2002). At the same time that the brain suggest that intraluminal pressure regulates cell proliferation which immediately leads us to ask how mechanistically this might come about.…”
Section: Introductionmentioning
confidence: 99%